HUBUNGAN LEUKOSIT DAN PROTEIN URINE PADA IBU HAMIL TRIMESTER III DI PUSKESMAS KLAMPIS BANGKALAN MADURA - Andreas Putro Ragil Santoso (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2019)
Most pregnant women give birth normally, but 15% of cases are life-threatening complications including preeclampsia. Preeclampsia is marked by an increase in proteinuria, whereas protein is closely related to leukocytes because the breakdown of proteins into amino acids is carried out by enzymes present in leukocytes, especially neutrophil cells. This study aims to determine the relationship between urine leukocyte levels and protein in urine in third trimester pregnant women. The research design used was analytic observation with a cross sectional approach. The study population was 35 Trimester III pregnant women in Madura klampis puskesmas, then determined based on the formula Slovin found 31 Trimester III pregnant women. The sampling technique is done using probability sampling technique. The results of research conducted based on the chi square test showed that the significance of p> 0.05 was 0.111 which showed that there was no relationship between leukocytes and urine protein in third trimester pregnant women.